Silicone elastomer formulations for improved performance of a multipurpose vaginal ring releasing dapivirine and levonorgestrel - Yahya H. Dallal Bashi; Diarmaid J. Murphy; Clare F. McCoy; Peter Boyd; Leeanne Brown; Matthew Kihara; François Martin; Nicole McMullen; Kyle Kleinbeck; Bindi Dangi; Patrick Spence; Bashir Hansraj; et al. (Elsevier, 2021)
A dapivirine-releasing silicone elastomer vaginal ring for reducing women's risk of HIV acquisition has recently been approved. A next-generation multipurpose vaginal ring releasing dapivirine and levonorgestrel is currently in development, offering hormonal contraception and HIV prevention from a single device. Previously, we reported challenges with incorporating levonorgestrel into rings manufactured from addition-cure silicone elastomers due to an irreversible chemical reaction between the levonorgestrel molecule and the hydride-functionalised crosslinker component of the silicone elastomer formulation, leading to low drug content assay, cure inhibition, and reduced ring mechanical properties (which may account for the increased incidence of ring expulsion in vivo). Here, we report on the development and testing of various custom silicone elastomer materials specifically formulated to circumvent these issues. After extensive testing of the custom silicones and subsequent manufacture and testing (Shore M hardness, pot life, content assay, oscillatory rheology, mechanical testing) of rings containing both dapivirine and levonorgestrel, a lead candidate formulation was selected that was amenable to practical ring manufacture via injection molding, exhibited no substantial levonorgestrel binding, and offered suitable mechanical properties.